PENDIDIKAN AGAMA (TAUHID) ANAK DALAM KELUARGA: STUDI KASUS DI KELURAHAN PONDOK BENDA PAMULANG TANGERANG SELATAN - Rachmatullah Rusli; Adam Sugiarto; Mudzakir; Sutikno (STAI Pelabuhan Ratu, 2023)
Religious Education (Tauhid) is one of the important programs that parents should provide to their children. It is the primary responsibility of parents to introduce their children to their God and instill love for their God, Allah, and His messenger Muhammad SAW, so that their pure nature can acknowledge the divinity of Allah. Through this religious education, children's souls are filled, enabling them to understand their own tasks and life purposes from an early age and behave according to His guidance. However, it is regrettable that nowadays many parents neglect religious education (Tauhid) within the family. Most parents consider education only focused on obtaining higher education that will facilitate finding a job, or they realize the importance of religious education (Tauhid) but start it too late. The purpose of this research is to determine the extent of the parents' role in teaching religious education (Tauhid) within the family and its implementation in daily life. This research uses a qualitative method, gathering data from interviews with several representative respondents. The research results indicate that the parents' background does not influence the process of teaching religious education (Tauhid) to their children. It is the awareness of faith that motivates parents to educate their children in religious matters (Tauhid). The facilities available at home, such as TV and smartphones, greatly influence the success of parents in educating their children in religious matters (Tauhid).